Analisis Tingkat Kebutuhan Pekerja Level Menengah Proyek Konstruksi (Studi Kasus: 3 Proyek Gedung di Jakarta Barat) - Irfanto, Ryobi; Salim, Felicia Devita (Universitas Ibn Khaldun, 2025)
The motivation of the workers influences the results of project work. The cause can be identified by knowing the level of needs of the workers. One way to find out the level of needs of workers is with Abraham Maslow's theory of needs. Abraham Maslow's ranking of needs consists of 5 levels of basic human needs, sequentially from the lowest level, namely physiological needs, safety, love and affection, esteem, and self-actualization. This study aims to analyze the level of needs for mid-level construction workers at Building Project in West Jakarta which affects the motivation of construction project workers. The research method used is a questionnaire to middle-level workers from three project. Data processing and literature analysis were carried out when the questionnaire indicators based on the literature were obtained on the 5 needs ratings. The results obtained from the questionnaire are that the most influential need factors for middle-level workers are support from family to workers, bonuses, good health programs, relations between co-workers, and overtime pay increased. By improving communication on the factors of need for support from family and good relations between co-workers, rewards on the factors of bonuses and overtime pay, last is guarantees a good health program on the factors of the work environment